2020
DOI: 10.3390/cells9020289
|View full text |Cite
|
Sign up to set email alerts
|

Urine microRNA Profiling Displays miR-125a Dysregulation in Children with Fragile X Syndrome

Abstract: A triplet repeat expansion leading to transcriptional silencing of the FMR1 gene results in fragile X syndrome (FXS), which is a common cause of inherited intellectual disability and autism. Phenotypic variation requires personalized treatment approaches and hampers clinical trials in FXS. We searched for microRNA (miRNA) biomarkers for FXS using deep sequencing of urine and identified 28 differentially regulated miRNAs when 219 reliably identified miRNAs were compared in dizygotic twin boys who shared the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 54 publications
(73 reference statements)
0
20
0
Order By: Relevance
“…There are twelve brain miRNAs identi ed to interact with FMRP in mouse brain including, miR-125a, miR-125b, and miR-132 [30]. To the best of our knowledge, there is only one published study on miRNA expression pro ling in FXS patients using deep sequencing [7]. In a most recent study Putkonen et al [7] showed upregulation of miR-125a in urine from children with FXS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are twelve brain miRNAs identi ed to interact with FMRP in mouse brain including, miR-125a, miR-125b, and miR-132 [30]. To the best of our knowledge, there is only one published study on miRNA expression pro ling in FXS patients using deep sequencing [7]. In a most recent study Putkonen et al [7] showed upregulation of miR-125a in urine from children with FXS.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is only one published study on miRNA expression pro ling in FXS patients using deep sequencing [7]. In a most recent study Putkonen et al [7] showed upregulation of miR-125a in urine from children with FXS. The investigators did not examine differential miRNA expression changes in FXS blood samples or the correlations of miR-125a levels in urine with those of in the cell-free circulation (i.e., in serum and plasma) and other body uids [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations